Optimasi Pengendalian Pengadaan Barang Consumable Menggunakan Metode Economic Order Quantity di PT. ZZ - Nurhanifah, Nida; Wahyudin, Wahyudin (Fakultas Teknik Universitas Tulang Bawang, 2024)
One of the most important things for companies, especially those operating in the manufacturing industry, is inventory. Often there is a shortage or excess of stock in companies when inventory control is still not optimal. PT. ZZ is a manufacturing company which supplies consumable goods with 1 inch paper duct tape as supporting goods in the excavator assembly process. These goods often experience stock shortages so that the production process is disrupted. To overcome this problem, it is necessary to carry out an analysis using the Economic Order Quantity (EOQ) approach to determine order size, order frequency, safety stock, and reorder point. The results obtained were a Total of 892.23 orders, with orders made twice a year and an interval of 130 days. Apart from that, a safety stock of 89 pcs was also produced and are order point of 115 pcs. Furthermore, according to company policy, all costs required to purchase consumable materials such as 1 inch paper duct tape are IDR 1,632,200. Meanwhile Rp. 290,196.61 is the amount needed if applying the EOQ approach. This means that the company can save IDR 1,342,003.39 if the company controls its procurement of goods using the EOQ approach. Keywords: Consumables, Economic order quantity, Inventory, Procurement